Formation of eugenics as a science : the world context - Fando, R. A. (History of science and technology, 2013)
The article is devoted to eugenics as a science in a world context. The conclusion is that eugenicis of the first half of the ХХ century is partly transformed in «prophylactic» human genetics and this union with general and medical genetics brings positive results all humanity.